Plea bargaining procedures worldwide: Drivers of introduction and use - Gabriele Paolini; Elena Kantorowicz-Reznichenko; Stefan Voigt (University of Hamburg, Institute of Law and Economics (ILE), 2023)
Over the last three decades, plea bargaining procedures have been adopted by a large number of jurisdictions worldwide. However, a comprehensive account of the current adoption and use of such procedures is still missing. We survey 174 jurisdictions, finding that 101 of them have a formalized plea-bargaining procedure. For 52 jurisdictions, we also compute a plea-bargaining rate, defined as the percentage of convictions imposed through plea bargaining over all criminal convictions imposed. By employing our novel dataset, we find that both a relative majority of Muslims in the population and the French and Scandinavian legal origins are associated with lower probabilities of formalizing plea bargaining. Regarding its use in practice, an increase in GDP per capita is associated with greater plea-bargaining rates up to a certain point, after which the relationship becomes negative. The Spanish and Socialist legal origins, a looser regulation of plea bargaining, and the presence of jury trials are all associated with higher plea-bargaining rates.
Keywords: 340; plea bargaining; Law and Economics; Empirical Legal Studies; criminal procedure; comparative law